Protein kinase C-alpha suppresses autophagy and induces neural tube defects via miR-129-2 in diabetic pregnancy - Fang Wang (Nature Portfolio, 2017)
Maternal diabetes can induce neural tube defects (NTD). Here, the authors show that in mice, deletion ofPrkca(encoding protein kinase C-alpha) restores autophagy, via suppression of miR-129-2 and reversal of reduced peroxisome proliferator-activated receptor c coactivator 1alpha, so reducing NTDs.